No polymorphisms in K13-propeller gene associated with artemisinin resistance in Plasmodium falciparum isolated from Brazzaville, Republic of Congo - Mayengue, Pembe Issamou (BMC Infect Dis, 2018)
BACKGROUND: In the Republic of Congo, artemisinin-based combinations have been recommended for the treatment of uncomplicated malaria since 2006. However, the emergence of resistant parasites again these combinations in Southeast Asia is a threat for the control of this disease, especially in sub-Saharan Africa where the weight of the disease is important. Indeed, polymorphisms in Plasmodium falciparum K13-propeller gene have been involved in variations of drug sensitivity of Plasmodium falciparum to artemisinin-based combinations. The aim of the current study is to determine the prevalence of mutations of this gene in isolates collected in three health centers in Brazzaville. METHODS: From May 2015 to May 2016, a total of 131, 259 and 416 samples from patients with suspected malaria were collected at the Laboratoire National de Santé Publique, Hôpital de Mfilou, and the CSI «Maman Mboualé» respectively. After DNA isolation, genotyping and sequencing of Plasmodium falciparum K13-propeller were performed in positive Plasmodium falciparum isolates identified after msp-2 gene genotyping. RESULTS: All 806 samples collected were msp-2 genotyped and Plasmodium falciparum infections were confirmed in 287 samples with 43, 85, 159 samples from Laboratoire National de Santé Publique, Hôpital de Mfilou, and the CSI «Maman Mboualé» respectively. Of these 287 msp-2 positives samples, K13-propeller nested PCR products were successfully obtained from 145 (50.52%) isolates and sequences were generated from 127(87.58%) nested products. None of mutations that were associated with ACTs resistance in Southeast Asia were detected on the samples from three different study sites from Brazzaville. However, one mutation type was observed at position 578, where alanine was substituted by serine (A578S) in two isolates (1.57%, 2/127), those from the Hôpital de Mfilou. No mutation was found in isolates from the two other sites. CONCLUSION: The current study shows a very limited polymorphism in the K13-propeller gene in isolates from the Republic of Congo and K13 polymorphisms associate with ACT resistance are not present in this country. However, permanent and large surveillance of resistant parasite population using K13-propeller gene is recommended.